Knowledge, Attitude and Practices of Medical Students Regarding Covid-19, Pakistan - Sarah Arif, Tayyaba Zia, Ghulam Mustafa, Zohaib Qayyum, Muhammad Ateeq, Mah Jabeen Faiz, Sudhair Abbas Bangash, Anila Farid, Fares M Muthanna, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: As a result of the COVID-19 epidemic, many people’s lives and livelihoods are at risk. All aspects of everyday life, including education, have been affected by the epidemic. Objective: As a result, we performed this cross-sectional study to learn more about how students from Khyber Pakhtunkhwa feel about COVID-19. Methods: This was a cross-sectional study in which respondents completed an online, self-administered form to get the information. Six questions deal with socio-demographics, fourteen ask about knowledge, seven ask about attitude, and eight ask about practice. Raosoft’s sample size calculator was used to calculate the final sample size. Results: Five thousand participants, comprising 2250 (45%) men and 2,750 (55%) women from all across the nation, completed this poll. Analysis of the data was done using a chi-square test. Almost all of the students 4750 (95 percent) were aware that COVID-19 is caused by a virus and that it is a respiratory illness 4600 (92 percent). During the lockout, many students continued to see their family members 2,750 (55 percent), and their family members continued to visit them at home 2950 (59 percent). The students’ answers to particular questions concerning the spread of the virus differed greatly. Although (p 0.01), women had more awareness about how to avoid illness transmission from patients who had been infected with the virus. Conclusion: In the wake of the COVID-19 epidemic, the vast majorities of college students were well-prepared, had a positive outlook, and were actively practicing their knowledge and skills. Aside from demographics and gender, the KAP scores also vary by family size. During times of crisis, it’s critical to keep the public informed about the need to practice preventive practices.